Pengaruh Pengalaman Belajar Metode Project-Based Learning Terhadap Minat Berwirausaha Mahasiswa Program Studi Sarjana Terhadap Kebidanan Kediri Poltekkes Kemenkes Malang - Barokah, Lia; Pratamaningyas, Susanti; Kundarti, Finta Isti; Hardjito, Koekoeh (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2025)
The high number of midwifery graduates and the limited job opportunities emphasized the need to develop entrepreneurial interest through innovative educational approaches such as the project-based learning method. The purpose of the studies was to analyze the effect of project-based learning experience on the entrepreneurial interest of student. A correlational quantitative approach with a cross-sectional design was used. The sample consisted of 60 final-year students from the Applied Midwifery Study Program in Kediri, selected using simple random sampling. Data were collected using a Likert-scale questionnaire and analyzed using the spearman rank correlation test. The results showed a significant relationship between Project-Based Learning experience and entrepreneurial interest (p = 0.000; r = 0.721). The greater the students' project-based learning experience, the higher their entrepreneurial interest. Project-based learning experience had a strong and positive influence on the entrepreneurial interest of midwifery students. These results indicate that the Project-Based Learning (PjBL) method is effective in fostering students’ active, collaborative, and creative attitudes, which are essential components in developing entrepreneurial interest. This finding reinforces the evidence that project-based learning is a relevant strategy to prepare midwifery graduates to be more independent and adaptive in facing the challenges of the job market.